The effect of malathion on the activity of cholinesterase from the freshwater Shrimp Caridina sp. - Mohd Khalizan Sabullah; Fisal Ahmad; Baskaran Gunasekaran; Abdul Rahim Abdul Rachman; Lee, Shi Yin; Siti Aqlima Ahmad; Mohd Yunus Shukor; Azlan Jualang Gansau; Mohd Rosni Sulaiman (2014)
Acetylcholinesterase (AChE) from Caridina sp. was tested for its sensitivity towards the anticholinesterase malathion. Prior to this study, optimal assay conditions were determined to be 25 oC, pH 8.0 and using phosphate buffer. At 10-8 M, malathion was able to inhibit AChE activity at 1.75% and this increased to 15.79% with the increasing of malathion concentration to 10-4 M. It is proven through this study that the crude extract of AChE is sensitive toward malathion exposure and provide an alternative source for biosensor development.